Committee on Transport Policy and Coordination Papers 71-140 - Planning Commission (Planning Commission, 1960)
The Chairman had an Informal meeting with Shri L.C. Kriplani, Transport, Controller, Delhi Administration at 10.00 A.M. on Saturday, the 2nd January, 1960. The Chairman desired to know whether in fixing the number of permits on Inter-State routes under reciprocal arrangements with the neighbouring States the Delhi Administration kept in view the interests of the Railways on the routes concerned.
Transport Division
Transport Division